Assessment of the iodine deficiency severity in the population by serum thyrotropin levels in newborns - T. V. Sorokman; M. I. Bachu; O. V. Makarova; N. O. Popeluk (Zaporožskij Medicinskij Žurnal)
The problem of iodine deficiency (ID) and its adverse effects on the Ukrainian population, especially on children, pregnant and lactating women, does not lose its relevance.